2020
DOI: 10.1021/acssensors.0c00058
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the Polydopamine Nanosphere/Aptamers Nanoplatform with a DNase-I-Assisted Recycling Amplification Strategy for Simultaneous Detection of MMP-9 and MMP-2 during Renal Interstitial Fibrosis

Abstract: Matrix metalloproteinase-9 (MMP-9) and matrix metalloproteinase-2 (MMP-2) play important roles in the progression of renal interstitial fibrosis (RIF). There is an increasing demand to construct a novel method for the simultaneous detection of MMP-9 and MMP-2 to monitor the progression of RIF. Herein, a strategy based on the nanoplatform composed of the polydopamine nanosphere and fluorescence-labeled aptamers is developed to simultaneously detect MMP-9 and MMP-2 with DNase-I-assisted recycling signal amplific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…Indeed, Du et al showed MMP-2 and MMP-9 levels increased over time in damaged tubules and lead to renal brosis, which is a typical phenomenon in progressive renal disease [31]. Other studies have shown MMP-2 plays a pathological role in interstitial renal brosis, probably by inducing EMT and macrophage in ltration [32]. In addition, Neal et al showed increased MMP-2, MMP-9, and TIMP-1 activity in the aorta of patients with progressive kidney disease, and increased activity of MMP-2 in the serum [33].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Du et al showed MMP-2 and MMP-9 levels increased over time in damaged tubules and lead to renal brosis, which is a typical phenomenon in progressive renal disease [31]. Other studies have shown MMP-2 plays a pathological role in interstitial renal brosis, probably by inducing EMT and macrophage in ltration [32]. In addition, Neal et al showed increased MMP-2, MMP-9, and TIMP-1 activity in the aorta of patients with progressive kidney disease, and increased activity of MMP-2 in the serum [33].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Du et al [32] showed MMP-2 and MMP-9 levels increased over time in damaged tubules and lead to renal fibrosis, which is a typical phenomenon in progressive renal disease. Other studies have shown MMP-2 plays a pathological role in interstitial renal fibrosis, probably by inducing epithelial-to-mesenchymal transition and macrophage infiltration [33]. In addition, Chen et al [34]showed increased MMP-2, MMP-9, and TIMP-1 activity in the aorta of patients with progressive kidney disease and increased activity of MMP-2 in the serum.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a strategy based on the nanoplatform composed of the PDA nanosphere and fluorescence‐labeled aptamers was developed to simultaneously detect MMP‐9 and MMP‐2 with DNase‐I‐assisted recycling signal amplification. [ 158 ]…”
Section: Pda Nanostructures With High Surface Areas Toward Adhesion‐driven Bioapplicationsmentioning
confidence: 99%
“…Likewise, a strategy based on the nanoplatform composed of the PDA nanosphere and fluorescence-labeled aptamers was developed to simultaneously detect MMP-9 and MMP-2 with DNase-I-assisted recycling signal amplification. [158] Significantly, one of the most significant development breakthroughs for PDA-based nucleic acid carriers could be the successful transition in the particle-oligonucleotide interaction designs from adsorption on the particles' outer surface to loading into the mesopores. After the controllable construction of new PDA nanostructures with porous structures developed by our team, we studied the porous PDA particles used in miRNA detection and comprehensively understood the pore-oligonucleotide interactions.…”
Section: Adhesion-based Sensing Delivery and Integration Of Biomacromolecules And Polymersmentioning
confidence: 99%